Pekerjaan Roh Kudus Bagi Pertumbuhan Iman (Studi Kisah Para Rasul) di GBI Metro Amplas Medan - Situmorang, Junaeka H.P; Ginting, Rahel Br (Jurnal Teologi dan Pendidikan Kristen, 2023)
The purpose of this study consists of three things, namely: The purpose of this study consists of three things, namely: whether there is a positive influence between the Understanding of the Work of the Holy Spirit in Acts on the growth of faith of members of GBI Metro Amplas, Medan. The research method is descriptive because it makes a systematic, factual, and accurate picture of the facts and nature of the respondent. This study used a non-experimental quantitative design because the data was readily available and could be calculated. From the results of the study obtained descriptively, namely: the value of the causal correlation of X and Y coefficients (rxy) was also greater after consultation with the Product Moment Table Value obtained interval level 95% 0.361 and confidence 95% 0.463 is 0.456 (0.456 > 0.361 and 0.463). The Influence Test has materialized, with results; percentage of influence of Variable X on Variable Y, r (dt) = 61.472% (positive influence). The congregation's understanding of the Holy Spirit's Work in Acts has a positive and significant influence on the Growth of Church Faith in GBI Metro Amplas, Medan.